Performance evaluation of anaerobic digestion and co-digestion of solid organic wastes in semicontinuosus reactors - Bres, Patricia Alina; Beily, María Eugenia; Butti, Mariano; Prieto, Matías Fernando; Candal, Roberto Jorge; Crespo, Diana Elvira (International Water Association, 2021)
Poster